Language Learning through AI Chatbots: Effectiveness and Cognitive Load Analysis - Safar, Muh.; Anggraheni, Dini (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The use of AI chatbots in language learning has gained popularity due to their accessibility and ability to provide interactive practice. However, concerns regarding their effectiveness in improving language skills and the potential cognitive load they place on learners remain underexplored. With the increasing integration of AI in education, understanding how these tools impact language acquisition is critical for optimizing learning outcomes. Purpose. This study aims to evaluate the effectiveness of AI chatbots in language learning and analyze the cognitive load experienced by learners during chatbot interactions. Method. A mixed-methods approach was used, combining quantitative assessments of language proficiency before and after using an AI chatbot for a three-week period, with qualitative interviews to assess learner perceptions of cognitive load. Participants included 60 university students learning a new language. Results. The results indicate that AI chatbots significantly improved language skills, particularly in conversational fluency and vocabulary acquisition. However, a moderate level of cognitive load was reported by learners, primarily due to the need to simultaneously engage in real-time conversation and process feedback. While the cognitive load was not overwhelming, it varied based on individual learner characteristics, such as prior language proficiency and familiarity with AI tools. Conclusion. In conclusion, AI chatbots offer an effective method for enhancing language learning, particularly in improving fluency and vocabulary. However, managing cognitive load is crucial to maximizing their educational potential. Further research is recommended to explore adaptive chatbot designs that can tailor interactions to individual learner needs.